Chemical variations in tension wood of poplar tree induced by intermittent bending, fertilizer and hormone treatments - Gorgij, Rahmatollah; Pourtahmasi, Kambiz; Amiri, Reza Maali; Abdulkhani, Ali; Timar, Maria Cristina; Coşereanu, Camelia (Universidad del Bio Bio, 2022)
Tree growth is influenced by various environmental factors that lead to anatomical, physical and chemical changes in their wood. Reaction wood is one of the tree's reactions that make many restrictions in wood usages. Reaction wood in broadleaf is called tension wood. This study was aimed to stimulate the formation of tension wood in two-year-old seedlings of Populus alba by using intermittent bending, nitrogen fertilization and gibberellin hormone. The application of different treatments increased the content of cellulose compared to the control sample. Meanwhile, the bent specimens had more increase while the straight specimens had no significant difference in the statistical grouping. The content of lignin decreased in all treatments compared to the control sample. The cellulose/lignin ratios obtained from ATR-FTIR (Attenuated Total Reflectance-Fourier Transform Infrared) analysis of wood sawdust and chemical composition measurements were almost close to each other and were higher in the treated samples than in the control. The degree of crystallinity obtained from XRD (X-ray Diffraction) measurements showed that all samples under intermittent bending had a significantly higher degree of crystallinity than the control sample, while this increase was not significant in all straight samples compared to the control sample. In general, it can be concluded that intermittent bending treatment had a greater effect on the stimulation and changes of chemical properties of tension wood in poplar and the application of nitrogen fertilization and gibberellin hormone increased this effect. The formation of gelatinous layer in the innermost part of the intermittent bent seedlings fiber cell wall was visible in light microscope images.
Keywords: Crystallinity; gibberellin; intermittent bending; nitrogen fertilization; poplar; tension wood